PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) PADA KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN SELF EFFICACY SISWA - Nisa', Kholifatun; Wisudaningsih, Endah Tri; Rahayu, Eka (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
The Think Pair Share (TPS) learning model aligns with the conditions of the Merdeka Curriculum. However, the application of this model is still limited and has not been widely measured through students' mathematical problem-solving ability and self-efficacy. Therefore, this study compares the effectiveness of the Think Pair Share (TPS) learning model and direct learning in improving students' mathematical problem-solving ability and self-efficacy. This study used a quantitative method with a Pre-test, Post-test Nonequivalent Control Group research design. The research subjects were taken through purposive sampling, involving two classes as samples. Class VIII D applies the Think Pair Share (TPS) learning model, and class VIII F uses direct learning. Data were obtained from pretest, posttest and questionnaire results. The collected data were then analyzed using the Independent Sample t-test and Pearson product-moment correlation test with a significance level of a = 0.05. The results of the analysis show that the significance value for mathematical problem-solving ability and student self-efficacy is below 0.05. It can be concluded that the Think Pair Share (TPS) learning model affects students' ability to understand, plan and solve a mathematical problem and can increase student self-efficacy based on this research.